A convention for international trade (based on Islamic Sufi teachings). Issue 5 (14th September 2015) - Bidabad, Bijan
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – This paper aims to propose a procedure to remove international trade barriers globally. Trade is confronting various barriers in the present world, and this is due to the policies of governments to protect interests of their own citizens. Experience shows that trade barriers end up with incurring losses for both sides (traders) in practice, but a look at history of polemics on trade barriers removal in World Trade Organization (WTO) shows that countries are unable to overcome the obstacles they have created. Trade partners understand that removal of counter barriers is advantageous for both parties. In the meantime, being concerned of other party's response impedes the benefits of free trade for all parties. Design/methodology/approach – This proposition is based upon Islamic Sufism teachings. The propounded principles and goals are in accordance with high understanding of social and economic subtleties of humankind's life. The authors try to form and formalize Islamic Sufi teachings to establish a base for compiling new international convention that facilitates international trade in all aspects. Findings – To facilitate and promote international trade relations in short run, interested countries may accept a convention to remove all trade barriers among themselves all at once. Research limitations/implications – The proposed convention does not go against General Agreement on Tariff and Trade and WTO, but it is complementary to both. Practical implications – The proposed principles are actually shortcuts to what WTO may access in far futures. Social implications – Islamic Sufism teachings can lead us to solve current international problems. Originality/value – WTO has taken important steps to facilitate international trade. To reach the main goal of trade liberalization of WTO, a shortcut solution is proposed here.